1936
DOI: 10.1021/ie50319a008
|View full text |Cite
|
Sign up to set email alerts
|

Water Impedance of Nitro-cellulose Films

Abstract: Mellon Institute and are tike average results of a number of tests on each type of material. For convenience in calculating heat losses for various mean temperature conditions, the conductivity of a few of these insulations is given in Figure 3. The thickness of insulation required to prevent sweating on the above air duct for any of the insulations whose conductivities are included will be found to be directly proportional to conductivities of the insulations chosen and the insulation used in calculating the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1937
1937
1943
1943

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…34 [ [26] 0. 04 [28] 1.1 [26] 2 [28] 22 [2] 44 [1] 68 [20] 150 [26] 1.4 [31] 6 [31] 15 [20] 10 [26] 20 [20] 42 [20] 0. 6 30] 100 [30] 75 [22] 100 [3] 105 [22] 120 [14] 21S [1] 251 [20 336 [14 1, 327 [1] 115 [14] 3.9 6.5 9.6 [23] 126 [20] 130 [14] i The numbers in brackets refer to the list of references at the end of the paper.…”
Section: Explanation Of Tablesmentioning
confidence: 99%
See 2 more Smart Citations
“…34 [ [26] 0. 04 [28] 1.1 [26] 2 [28] 22 [2] 44 [1] 68 [20] 150 [26] 1.4 [31] 6 [31] 15 [20] 10 [26] 20 [20] 42 [20] 0. 6 30] 100 [30] 75 [22] 100 [3] 105 [22] 120 [14] 21S [1] 251 [20 336 [14 1, 327 [1] 115 [14] 3.9 6.5 9.6 [23] 126 [20] 130 [14] i The numbers in brackets refer to the list of references at the end of the paper.…”
Section: Explanation Of Tablesmentioning
confidence: 99%
“…Evidence that such a relation does not hold is found [23], although others have concluded that the relation may or may not hold, depending upon the type of testing method used, the nature of the material, and the effect of sorption at high humidities [26]. Other workers report that the moisture impedance (reciprocal of the permeability) is substantially proportional to the thickness or linearly related to it [31,33].…”
Section: Leakage At the Edgesmentioning
confidence: 99%
See 1 more Smart Citation